Finns det på nätet? - Skott, Fredrik (Tidsskrift for kulturforskning, 2014)
Internet offers a range of new opportunities for the folklore archives. Through online publishing the archives make their collections of folklore records, answers of questionnaires, interviews etc. more easily accessible than ever before. More people can get access to the collections and new groups of potential users can be reached. In many cases the archives are also expected to give priority to put material online, both by the public, researchers and the governments. The methods for publishing folklore collections on Internet are discussed from a critical point of view. Ethical problems are treated, not least the need to relate to old promises not to spread the material, and also possible consequences of anonymousness and selection as methods for protecting individuals or groups who have contributed to or are mentioned in the material. The text also argues that online publishing folklore collections should not only be regarded as a method for making the material available. Through putting collections online the archives produce history and thus contribute to create intangible cultural heritage.